Legal Analysis of the Determination of Suspects by Investigators: Case Study at Polsek Medan Timur, Indonesia - Christin Joys Vanka Sianipar; D. Debora (Golden Ratio of Data in Summary, 2026)
The determination of suspects is a crucial stage that has an impact on human rights and the legitimacy of law enforcement. This study analyzes the procedure for determining suspects based on evidence, identifies challenges, and formulates solutions at the Medan Timur Police Station. The method used is qualitative empirical law. Primary data were obtained from interviews with experienced investigators, while secondary data were obtained from regulations, court decisions, and relevant literature. Normatively, the mechanism for determining suspects refers to the Criminal Procedure Code, Constitutional Court decisions, and Chief of Police regulations, which require the fulfillment of two pieces of evidence and a case title. However, empirically, three main challenges were identified: the limited technical capacity of investigators in handling technological evidence, inadequate infrastructure, and public and media pressure in high-profile cases. The findings indicate that witness testimony remains dominant, while digital evidence is not yet fully optimized. It is concluded that the case title acts as an internal filter, but does not fully counteract external pressure. Therefore, it is necessary to strengthen the capacity of investigators, optimize investigation facilities, and increase public legal awareness to ensure the professional, accountable, and fair determination of suspects.